Analisis Biaya Struktur Bawah: Perbandingan Rab Fondasi Batu Kali Dan Fondasi Lajur Beton Pada Rumah Sederhana Tipe 36 (Studi: Belopa) - Firdha Sudirman; Anggel Erpa Erong Pakiding (Jurnal Ilmu Teknik Sipil Indonesia, 2026)
The substructure is an essential part of building construction that serves as a which transfers building loads safely to the underlying soil. This study aims to analyze the cost comparisons between two types of foundations commonly used in simple type 36 house, namely stone foundation and concrete strip foundation. The method used was quantitative comparative analysis by calculating the Cost Budget Plan (RAB) of both types of foundations based on work volume and unit price of materials as well as labor wages. The results of the study showed that total cost of stone foundation amounted to IDR24,725,953 while concrete strip foundation was IDR39,475,448 hence there is a difference in cost of IDR14,749,495. Based on these results, stone foundations are more economical for simple homes in stable soil conditions, while concrete strip foundations are better suited to buildings that require higher structural strength.